2022
DOI: 10.3390/app12020692
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Bidirectional Performance of Hotel Attributes through Online Reviews Based on Sentiment Analysis and Kano-IPA Model

Abstract: As people increasingly make hotel booking decisions relying on online reviews, how to effectively improve customer ratings has become a major point for hotel managers. Online reviews serve as a promising data source to enhance service attributes in order to improve online bookings. This paper employs online customer ratings and textual reviews to explore the bidirectional performance (good performance in positive reviews and poor performance in negative reviews) of hotel attributes in terms of four hotel star … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Satisfiers: 0.1<IA≤0.4 (10) Delighters: IA>0.4 (11) As depicted in Table 1, it is clear that seven out of ten attributes have significantly changed in impactasymmetry after experiencing the pandemic. Only three "Satisfiers" attributes, "service", "food," and "staff," were assessed as having no significant change across the three stages of the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfiers: 0.1<IA≤0.4 (10) Delighters: IA>0.4 (11) As depicted in Table 1, it is clear that seven out of ten attributes have significantly changed in impactasymmetry after experiencing the pandemic. Only three "Satisfiers" attributes, "service", "food," and "staff," were assessed as having no significant change across the three stages of the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…While the three-factor theory has been accepted and applied in various travel fields, some studies suggest that the degree to which an attribute affects customer satisfaction may vary in different contexts [10] . Chen et al (2022) found that hotel attributes contributing to high/low customer ratings differed among hotels with different star ratings [11] .…”
Section: The Asymmetric Impacts Of Hospitality Services On Customer S...mentioning
confidence: 99%
“…The proposed methodology comprises four main components: data acquisition, preprocessing, classification, and evaluation. For sentiment analysis, different forms of data are examined by the research community, including Tweets [ 10 – 14 ], movie reviews [ 15 , 20 , 38 ], Amazon product reviews [ 23 , 32 ], TripAdvisor Reviews [ 45 ], Short Messages [ 43 ], and Hotel Reviews [ 53 ]. This research methodology considered a renowned dataset of tweets for detailed experimentation and evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Their technique converted textual reviews into sentiment scores, which distinguished the actual hotel attributes that contributed to star ratings. According to their selection criteria, adjectives, adverbs, nouns, and verbs were exploited as candidate sentiment words [ 53 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of sentiment analysis were used together with word frequency statistics to dynamically measure the customer satisfaction with hotels. Chen et al [58] built a new sentiment lexicon for hospitality using the PolarityRank algorithm and performed sentiment analysis on a large dataset of online reviews of London hotels. The sentiment analysis result was used as attribute performance in the Kano-IPA model to explain customers' rating behaviors and prioritize attributes for improvement.…”
Section: Text Mining Of Online Hotel Reviewsmentioning
confidence: 99%